Pengaruh Kepedulian Lingkungan terhadap Pilihan Konsumen dalam Mengatasi Darurat Sampah di Yogyakarta (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
This study examines the influence of environmental concern on consumer choice in overcoming waste problems in Yogyakarta, with knowledge of waste management as a mediating variable. Using a quantitative approach and the SEM-PLS model, data were collected from 309 student respondents. The results show that environmental concern has a positive and significant effect on the choice of environmentally friendly products. Knowledge of waste management also strengthens this relationship as a mediator, supporting the Stimulus-Organism-Response (SOR) theoretical framework. The findings underscore the importance of increasing public knowledge and awareness related to waste management to encourage sustainable behavior. This study recommends the development of educational programs and campaigns that focus on emotional aspects and environmental knowledge. However, limitations such as limited sampling and non-random sampling should be considered for further research so that the results are more representative and in-depth in understanding the factors that influence sustainable consumption behavior in the area.
Keywords: Environmental Awareness; Waste Processing Knowledge; Choice of Environmentally Friendly Product Containers; SOR